The 2009 L'Aquila earthquake (central Italy): A source mechanism and implications for seismic hazard - Walters, R; Elliott, J; D'Agostino, N; England, P; Hunstad, I; Jackson, J; Parsons, B; Phillips, R; Roberts, G (2009)
We use InSAR and body-wave seismology to determine independent source parameters for the 6th April 2009 Mw 6.3 L'Aquila earthquake and confirm that the earthquake ruptured a SW-dipping normal fault with ∼0.6-0.8 m slip. The causative Paganica fault had been neglected relative to other nearby range-frontal faults, partly because it has a subdued geomorphological expression in comparison with these faults. The L'Aquila earthquake occurred in an area with a marked seismic deficit relative to geodetically determined strain accumulation. We use our source model to calculate stress changes on nearby faults produced by the L'Aquila earthquake and we find that several of these faults have been brought closer to failure. Copyright 2009 by the American Geophysical Union.